Improved measurement of absolute branching fraction of Ds+→τ+ν τ - Onyisi, P; Rosner, J; Alexander, J; Cassel, D; Duboscq, J; Ehrlich, R; Fields, L; Galik, R; Gibbons, L; Gray, R; Gray, S; Hartill, D; et al. (2009)
We have studied the leptonic decay Ds+→τ+ντ, via the decay channel τ+→e+νeν̄τ, using a sample of tagged Ds+ decays collected near the Ds*±Ds peak production energy in e+e- collisions with the CLEO-c detector. We obtain B(Ds+→τ+ντ)=( 5.30±0.47±0.22)% and determine the decay constant fDs=(252.5±11.1± 5.2)MeV, where the first uncertainties are statistical and the second are systematic. © 2009 The American Physical Society.